2005
DOI: 10.1093/humrep/dei293
|View full text |Cite
|
Sign up to set email alerts
|

The use of recombinant human LH (lutropin alfa) in the late stimulation phase of assisted reproduction cycles: a double-blind, randomized, prospective study

Abstract: In this patient population, the addition of r-hLH during the late follicular phase of a long GnRH agonist and r-hFSH stimulation cycle provides no further benefit in terms of oocyte maturation or other end-points.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
1
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 26 publications
3
37
1
2
Order By: Relevance
“…Four trials fulfilled the inclusion criteria [2,[8][9][10]. In 3 trials, the pituitary down-regulation with GnRH-a started in the mid-luteal phase of the preceding cycle and in 1 trial in the beginning of the menstrual cycle.…”
Section: Search Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Four trials fulfilled the inclusion criteria [2,[8][9][10]. In 3 trials, the pituitary down-regulation with GnRH-a started in the mid-luteal phase of the preceding cycle and in 1 trial in the beginning of the menstrual cycle.…”
Section: Search Resultsmentioning
confidence: 99%
“…Tarlatzis et al [10] The trial was a double-blind, randomized, placebo-controlled, prospective study performed at six centres in four countries. Women were eligible for inclusion in the study if they aged between 18 and 37 years, had a normal uterus and two ovaries, and were scheduled to undergo controlled ovarian stimulation prior to IVF with ICSI.…”
Section: Search Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This question was raised by the consideration that oocyte retrieval for ART, which offers a precious opportunity to collect granulosa cells, is frequently carried out from preovulatory follicles few hours before ovulation [32,33]. In these cases, as reported for human LGC [17], the follicles are punctured well after the gonadotropin treatment that mimic the LH pre-ovulatory surge, i.e.…”
Section: New Bone Formation In Vivomentioning
confidence: 99%
“…Multiple permutations of FSH and LH administration during the mid-and late follicular phases have been investigated with varying degrees of success in obtaining oocytes with embryonic developmental competence and efficiency of establishing pregnancies [16][17][18][19][20]. Several studies have demonstrated that administration of LH activity alone or combined with FSH can exert significant actions on folliculogenesis [10,21].…”
Section: Introductionmentioning
confidence: 99%